If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + -1) = 11(2x + -8) Reorder the terms: 4(-1 + 6x) = 11(2x + -8) (-1 * 4 + 6x * 4) = 11(2x + -8) (-4 + 24x) = 11(2x + -8) Reorder the terms: -4 + 24x = 11(-8 + 2x) -4 + 24x = (-8 * 11 + 2x * 11) -4 + 24x = (-88 + 22x) Solving -4 + 24x = -88 + 22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22x' to each side of the equation. -4 + 24x + -22x = -88 + 22x + -22x Combine like terms: 24x + -22x = 2x -4 + 2x = -88 + 22x + -22x Combine like terms: 22x + -22x = 0 -4 + 2x = -88 + 0 -4 + 2x = -88 Add '4' to each side of the equation. -4 + 4 + 2x = -88 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = -88 + 4 2x = -88 + 4 Combine like terms: -88 + 4 = -84 2x = -84 Divide each side by '2'. x = -42 Simplifying x = -42
| 2x+5+6x= | | 9x-5(2x-2)=70 | | 8+4(9d-4)=10 | | 21x+6(4x+2)=-6 | | (5p+28)+x=180 | | -3(7a+9)-15a=0 | | 12m(m)(m)-8m(m)-15m=o | | 2(4w+3)-11=19 | | (7-2x)(28-2x)=130 | | 4-(3c-6)=7c | | 4x^2-70x+66=0 | | -5(2a-12)=130 | | -10.4+3.2f=5f+4 | | (5p+28)=12p | | 3(-4y+9)=-30y | | 2/3+1/4t=1/3 | | 2(8d-33)=22 | | (p-2q)2-10(p-2q)+24= | | 36k(k)-25=0 | | 5c^2+38c+48=0 | | -13x+37-20x=8x-44-5x | | 16.3k+19.2+17.5k=-64.1 | | .3x-0.2(3-5x)=-.05(x-6) | | 9c-6+7c=5+9c-11 | | 6x^2+5x-10=0 | | -2w-4-8w=10w+16 | | 11c+24-3c=3c+49 | | 4-3a=4+6a | | -6x=17-3x | | 10x+15-3x+18=60 | | 5c+6=-4-5c | | 3-9(x+1)-3=3+3(9-3x)-81 |